MedLinac2: a GEANT4 based software package for radiotherapy - Barbara Caccia; Claudio Andenna; Giuseppe Antonio Pablo Cirrone (Istituto Superiore di Sanità, 2010)
Dose distribution evaluation in oncological radiotherapy treatments is an outstanding problem that requires sophisticated computing technologies to optimize the clinical results (i.e. increase the dose to the tumour and reduce the dose to the healthy tissues). Nowdays, dose calculation algorithms based on the Monte Carlo method are generally regarded as the most accurate tools for radiotherapy. The flexibility of the GEANT4 (GEometry ANd Tracking) Monte Carlo particle transport simulation code allows a wide range of applications, from high-energy to medical physics. In order to disseminate and encourage the use of Monte Carlo method in oncological radiotherapy, a software package based on the GEANT4 Monte Carlo toolkit has been developed. The developed package (MedLinac2) allows to simulate in an adequate flexible way a linear accelerator for radiotherapy and to evaluate the dose distributions.